Timing of definitive fixation of major long bone fractures: Can fat embolism syndrome be prevented?. (June 2017) - Blokhuis, Taco J.; Pape, Hans-Christoph; Frölke, Jan-Paul
Abstract: Fat embolism is common in patients with major fractures, but leads to devastating consequences, named fat embolism syndrome (FES) in some. Despite advances in treatment strategies regarding the timing of definitive fixation of major fractures, FES still occurs in patients. In this overview, current literature is reviewed and optimal treatment strategies for patients with multiple traumatic injuries, including major fractures, are discussed. Considering the multifactorial etiology of FES, including mechanical and biochemical pathways, FES cannot be prevented in all patients. However, screening for symptoms of FES should be standard in the pre-operative work-up of these patients, prior to definitive fixation of major fractures.